Sexualidade, currículo e redemocratização: lutas e debates para a implementação do Projeto de Orientação Sexual no governo de Luiza Erundina (1989-1992) - Delbem, Valéria Conte (2024)
This research proposes to analyze the constitution of the Sexual Orientation Project in the city of São Paulo during the Paulo Freire administration and succeeded by Mário Sérgio Cortella, at the head of the Education Secretariat in the context of Brazilian redemocratization, between the years 1989-1992, marked by the beginning and end of PT management in the municipality. The work intends to be a historical and documentary study of the path taken to implement the project, the debates established by the study groups in this formulation and the material formulated for the project. The research hypothesis is that the implementation of the program occurred in a context of struggles and disputes between various social actors and their political representations, which also reflected the turbulent historical moment of the country's political opening in relation to the need for knowledge of the body in conjunction with themes “sensitive”, AIDS, teenage pregnancy, sexually transmitted diseases (STDs). The work consists of a study of documents that were part of the construction of the project, such as newspapers, notebooks, opinions, minutes and debates of study groups and commissions, culminating in the creation of a sexual orientation notebook in which there was a description of the work of educators and in the approval of the Common School Regulations, by Municipal Decree No. 32,892, of December 23, 1992, by Mayor Luiza Erundina. The work is based on the concept of curriculum prescribed in Goodson (2011), which explains that the curriculum is a social technology developed in action, time, place and historical context, supported by a set of discourses, documents, stories and practices linked to the school process. As a result of the research, it was observed that the Sexual Orientation Project, in its time, introduced important debates in schools that expanded the view on sex and sexuality, a field, until then, dominated by health and the perspective of controlling bodies, reaching a significant number of students in the city of São Paulo, through an interdisciplinary path